Vladimir Carvalhos Sertões and I (Revista Internacional de Folkcomunicação, 2023)
This interview is a product of two meetings in may 2022 in Brasilia and a third one via GoogleMeet, when Vladimir Carvalho offered a masterclass in the openning of a seminar hold by  Universidade Federal do Rio Grande do Norte (UFRN). We took advantage of the presential meetigns aiming at carry  on structured or semistructure dialogues (interviews) as we walked by the streets, blocks and his own archive instituton in Brazil´´´'s capital, where he stoks a great amount of visual documents generated by his working as film-maker, together with  letters, books, posters and audiovisual materail from all over the world. Our peripathetic trail was crossed by a sort of dialogue in which during our vivid walking observations of modernists buildings and the live images refered by Carvalho I tried to process as a knowledge came both from historic monumental facts and  personal memory with the powerfull traces of turning into a hybrid discoursibe genre between journalism and scientific modes. Given the strong  Northeastern origins he bears as a stand point, folk manifestations from Sertão and the Coast side of his regions, culture industry popular and national geopolitical which displaced millios from the North to the Brasila region were both the traces what outlined his works as an artist and, consequently,  our conversation.